Cutting Edge: Brucella abortus Exploits a Cellular Prion Protein on Intestinal M Cells as an Invasive Receptor - Nakato, Gaku; Hase, Koji; Suzuki, Michio; Kimura, Masanobu; Ato, Manabu; Hanazato, Misaho; Tobiume, Minoru; Horiuchi, Motohiro; Atarashi, Ryuichiro; Nishida, Noriyuki; Watarai, Masahisa; Imaoka, Koichi; et al. (The Journal of immunology (1950), 2012)
Brucella abortus is a Gram-negative bacterium causing brucellosis. Although B. abortus is known to infect via the oral route, the entry site in the gastrointestinal tract has been unclear. We found that B. abortus was selectively internalized by microfold cells (M cells), a subset of epithelial cells specialized for mucosal Ag uptake. During this process, colocalization of cellular prion protein (PrPC) and B. abortus was evident on the apical surface as well as in subapical vacuolar structures in M cells. Internalization of B. abortus by M cells of PrPC-deficient (Prnp−/−) mice was greatly reduced compared with that in wild-type mice. Furthermore, an oral infection study revealed that translocation of B. abortus into the Peyer’s patch was significantly lower in Prnp−/− than in wild-type mice. These observations suggest that orally infected B. abortus invades the host through M cells by using PrPC on the apical surface of M cells as an uptake receptor.